SIMULASI DIAMETER GEL BASAH PADA FABRIKASI KERNEL YTTRIA-STABILIZED ZIRCONIA MENGGUNAKAN ALAT GEL-CASTING - Yusnitha, Erilia; Sarjono; Susilowati, Sri Rinanti; Dewayatna, Winter; Sediawan, Wahyudi Budi (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
In kernel fabrication, microsphere of gelled kernels (yttria-stabilized zirconia) were made by droplet formation of the broth through the gel-casting equipment. Broth is feed of gel-casting equipment that were made of mixed of zirconium (IV) nitrate, yttrium (III) nitrate hexahydrate, urea, tetrahydrofurfuryl alcohol (THFA), and poly vinyl alcohol (PVA). The process parameter of the gel-casting equipment such as vibration frequency and broth flowrate need to be set up to control shape and diameter of the targeted microsphere of gelled kernels. The gel-casting equipment at PTBBN – BATAN is equipped with single nozzle with 1 mm diameter. The simulation work is important to be carried out to reduce the number of experiments in the laboratory hence it reduces the waste from trial and error in the experiment. Moreover, the objective of this simulation work is to predict the diameter of microsphere of gelled kernels. Therefore, the simulation of microsphere of gelled kernel diameter is necessary to be build and verified with the experiment data. According to hypothesis, the simulation of microsphere of gelled kernel diameter can be conducted by considering gel-casting equipment parameter such as the broth flowrate and vibration frequency. In addition, the broth characteristic as broth density affects the diameter of microsphere of gelled kernels diameter. The diameter of microsphere of gelled kernels produced from gel-casting equipment were determined with digital microscope. The result from simulation calculation shows that diameter of microsphere of gelled kernels produced from laboratory experiment can be approached by modified equation involving vibration frequency, broth flowrate, metal concentration in the broth and broth density. It appears that the deviation of simulation calculation is smaller than simple equation, where only vibration frequency and broth flowrate are included in the calculation.